Supporting Boys as Readers. (23rd August 2013) - Serafini, Frank
Abstract: The challenges associated with boys and reading are focused on such factors as society's lack of focus on literacy skills, parents failings to inspire reading in boys, and internal motivational factors rather than looking at the environments created for reading in and out of school. In this column, several ideas for helping boys develop a sense of themselves as readers and get the books they want into their hands are offered. Ten instructional strategies are presented for supporting boys as readers.